Interactions between COVID-19 infection and diabetes - Heshmati, Hassan M. (Frontiers in Endocrinology, 2024)
Coronavirus disease 2019 (COVID-19) caused a major pandemic affecting human health and economy around the world since the beginning of 2020. The virus responsible for the disease is “severe acute respiratory syndrome coronavirus 2” (SARS-CoV-2). It invades the target cells by binding to angiotensin-converting enzyme 2 (ACE2). ACE2 is expressed in several organs including endocrine glands. Multiple endocrine and metabolic systems including the endocrine pancreas have been impacted by COVID-19 infection/pandemic. COVID-19 pandemic can promote obesity through alterations in lifestyle (e.g., unhealthy diet and reduced physical activity due to confinement and isolation) leading to type 2 diabetes and/or can directly impair the function of the endocrine pancreas particularly through a cytokine storm, promoting or aggravating type 1 or type 2 diabetes. The increased ACE2 receptors of high adiposity commonly associated with type 2 diabetes and the chronic hyperglycemia of diabetes with its negative impact on the immune system can increase the risk of COVID-19 infection and its morbidity/mortality. In conclusion, there are bidirectional interactions between COVID-19 pandemic and diabetes (e.g., COVID-19 infection can impact diabetes and diabetes can impact COVID-19 infection). The services offered by healthcare systems for the management of diabetes have been adapted accordingly.